The Influence of Financial Performance on Stock Prices of Financing Service Sub-Sector Companies - Jumriana, Jumriana; Matyani, Matyani; Sofyaun, Ashari (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to determine the effect of financial performance on stock prices. The population of this study is 15 companies and based on the sample criteria, there are 13 Financing Service subsector companies listed on the Indonesia Stock Exchange that meet the criteria. This study uses a quantitative method with multiple linear regression analysis using SPSS 25. The results of the analysis show that the Current Ratio and Debt to Equity Ratio variables do not affect stock prices. Return on Asset and Earnings Per Share have a significant effect on stock prices in financing service subsector companies.